Uptake and outcomes of a prevention-of mother-to-child transmission (PMTCT) program in Zomba district, Malawi - Gawa Lucy; Landes Megan; Bedell Richard; van Lettow Monique; Gatto Stephanie; Mayuni Isabell; Chan Adrienne K; Tenthani Lyson; Schouten Erik (BMC, 2011)
Abstract Background HIV prevalence among pregnant women in Malawi is 12.6%, and mother-to-child transmission is a major route of transmission. As PMTCT services have expanded in Malawi in recent years, we sought to determine uptake of services, HIV-relevant infant feeding practices and mother-child health outcomes. Methods A matched-cohort study of HIV-infected and HIV-uninfected mothers and their infants at 18-20 months post-partum in Zomba District, Malawi. 360 HIV-infected and 360 HIV-uninfected mothers were identified through registers. 387 mother-child pairs were included in the study. Results 10% of HIV-infected mothers were on HAART before delivery, 27% by 18-20 months post-partum. sd-NVP was taken by 75% of HIV-infected mothers not on HAART, and given to 66% of infants. 18% of HIV-infected mothers followed all current recommended PMTCT options. HIV-infected mothers breastfed fewer months than HIV-uninfected mothers (12 vs.18, respectively; p < 0.01). 19% of exposed versus 5% of unexposed children had died by 18-20 months; p < 0.01. 28% of exposed children had been tested for HIV prior to the study, 76% were tested as part of the study and 11% were found HIV-positive. HIV-free survival by 18-20 months was 66% (95%CI 58-74). There were 11(6%) maternal deaths among HIV-infected mothers only. Conclusion This study shows low PMTCT program efficiency and effectiveness under routine program conditions in Malawi. HIV-free infant survival may have been influenced by key factors, including underuse of HAART, underuse of sd-NVP, and suboptimal infant feeding practices. Maternal mortality among HIV-infected women demands attention; improved maternal survival is a means to improve infant survival.